Effects of elastic band resistance training on the physical and mental health of elderly individuals: A mixed methods systematic review. - Aiying Li; Yan Sun; Meng Li; Dongyang Wang; Xiaofeng Ma (PLoS ONE)
Objectives Elastic band resistance training in elderly individuals can improve physical fitness and promote mental health in addition to other benefits. This systematic review aimed to review, summarize, and evaluate quantitative, qualitative, and mixed methodological studies on the use of elastic band resistance training in elderly individuals, and to investigate the influence of elastic band resistance training on the physical and mental health of elderly individuals, as well as their preferences and obstacles in training. Methods A convergent separation approach was used to synthesize and integrate the results, specifically the mixed systematic review approach recommended by the Joanna Briggs Institute. The extensive search strategy included electronic database searches in the Cochrane Library, PubMed, Embase, Web of Science, Google Scholar, MEDLINE, and CINAHL. The researchers rigorously screened the literature, extracted and analyzed the data, and evaluated the quality of the included studies using the Mixed Methods Appraisal Tool (MMAT). Results Twenty-eight studies were included, of which 25 were quantitative studies, 2 were qualitative studies, and 1 was a mixed-methods study. A total of 1,697 subjects were investigated across all studies. Quantitative evidence supports the notion that elastic band resistance training can improve upper and lower limb flexibility, endurance, upper strength, physical balance, and cardiopulmonary function and enhance the mental health of elderly individuals. Participants in the qualitative study reported some preferences and obstacles with band resistance training, but most participants reported physical benefits. Conclusions Despite the heterogeneity between studies, this review is the first systematic review to comprehensively evaluate the effectiveness of elastic band resistance training in older adults. It not only shows the influence of elastic band resistance training on the physical and mental health of the elderly, but also emphasizes the preference and obstacles of elderly individuals face.